Traditional Health Care System of Pando tribes of Chhattisgarh: A Sociological Studies - Dr.R.N.SHARMA (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2025)
Still today some of the tribal society living in dense terrains for away from modern civilization is treating themselves by various method like- forest herbs witchcrafts and black-magic. Sociologists called it their traditional method of treatment. Impact of modern civilization has also not distorted their faith on their traditional methods. They believe that their traditional health care practitioners to whom they called ‘Bhaigas’, ‘Ghunias’ or ‘Dewar’ possess supernatural powers , can only relief them from all types of health related problems. It has been always challenging for human society to be free from disease. Since the beginning of human civilization, man is trying his level best to over come disease or discomforts. Thousands of years ago from now when science was in its infancy, man has been treating maladies, illness and disorders through herbs, black- magic and other rites & rituals. With reference to tribal societies views regarding health-matter also symbolizes social-cultural specialties. In the present research paper an attempt has been made to analyze the traditional methods and views of Pando tribes inhabiting Surguja district of Chhattisgarh.